Ternary positive electrode material, preparation method thereof and electrochemical device

By using nano-scale high-nickel ternary cathode material precursor and solid electrolyte, tin oxide and soluble cobalt salt coating technology, the problem that existing ternary cathode materials are difficult to meet the high specific capacity and high power at the same time is solved, and the problem of high specific capacity and high power is achieved. Compatible with high energy density and excellent power performance.

CN119490238APending Publication Date: 2025-02-21NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702970.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing nickel-cobalt-manganese ternary cathode materials are difficult to meet the dual needs of high specific capacity and high power at the same time, and cannot fully adapt to the complex application scenarios of electric vertical take-off and landing aircraft (EVTOL) batteries.

Method used

The precursor of nano-scale high-nickel ternary positive electrode material is used as raw material, and the core is formed by primary sintering, and then the mixed coating material of solid electrolyte, tin oxide and soluble cobalt salt is secondary sintered to form a cladding layer, which increases the three Specific capacity and rate performance of the cathode material.

Benefits of technology

It realizes compatibility between high specific capacity and high rate performance of ternary positive electrode materials. The electrochemical device has high energy density and excellent power performance, and is suitable for high power and high energy density application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490238A_ABST
    Figure CN119490238A_ABST
Patent Text Reader

Abstract

The invention provides a ternary positive electrode material, a preparation method thereof and an electrochemical device, the preparation method of the ternary positive electrode material provided by the embodiment of the invention comprises the following steps: mixing a nanoscale ternary positive electrode material precursor with a lithium source to obtain a mixed material, and carrying out primary sintering on the mixed material to obtain an inner core, the chemical formula of the ternary positive electrode material precursor is Ni [alpha] Co [beta] Mn [gamma] (OH) 2, and the chemical formula of the ternary positive electrode material precursor is Ni [alpha] Co [beta] Mn [gamma] (OH) 2. 0.8 < = alpha < lt >; 0.9, 0.1 lt; beta is less than or equal to 0.2, 0.01 lt; gamma < = 0.1, and beta + gamma < = 0.2; mixing and grinding a solid electrolyte, a tin-containing oxide and a soluble cobalt salt to obtain a coated material; and mixing the inner core and the coating material, and carrying out secondary sintering to form a coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material. The ternary positive electrode material prepared by taking the nanoscale ternary positive electrode material precursor as a raw material and taking the solid electrolyte, the tin-containing oxide and the soluble cobalt salt as coating materials has excellent capacity and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy materials, and in particular to a ternary positive electrode material and a preparation method thereof, and an electrochemical device. Background Art

[0002] As an emerging technology in the aviation field, electric vertical take-off and landing aircraft (EVTOL) has great application prospects. Compared with new energy electric vehicles, EVTOL requires batteries with higher energy density to solve the limitation of battery energy density on the range of aircraft. In addition, in order to meet the needs of EVTOL emergency landing and frequent use scenarios, EVTOL also puts forward higher requirements on the power performance of lithium-ion batteries.

[0003] At present, batteries using nickel-cobalt-manganese ternary positive electrode materials are the most widely used in EVTOL. However, this type of battery, whether it is a high-cobalt and low-nickel ternary positive electrode material or a high-nickel ternary positive electrode material, is difficult to simultaneously meet the dual requirements of high specific capacity and high power, and cannot be fully applied to the complex application scenarios of the above-mentioned EVTOL batteries. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a ternary positive electrode material.

[0005] The embodiments of the present application provide a ternary positive electrode material prepared by the aforementioned method for preparing the ternary positive electrode material, and an electrochemical device using the ternary positive electrode material.

[0006] The present application also provides a method for preparing a ternary positive electrode material, comprising: A nanometer-scale ternary cathode material precursor is mixed with a lithium source to obtain a mixed material, and the mixed material is sintered once to obtain a core, wherein the chemical formula of the ternary cathode material precursor is Ni α Co β Mnγ(OH) 2 , 0.8≤α<0.9, 0.1<β≤0.2, 0.01<γ≤0.1, and β+γ≤0.2; Mixing and grinding a solid electrolyte, a tin-containing oxide and a soluble cobalt salt to obtain a coated material; and The inner core and the coating material are mixed and subjected to secondary sintering to form a coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material.

[0007] In some possible embodiments, before the step of mixing the nanoscale ternary cathode material precursor with the lithium source and performing a sintering, the preparation method further comprises: The ternary positive electrode material precursor is crushed by air flow crushing to obtain a nano-scale ternary positive electrode material precursor. The parameters of the air flow crushing include: a feed rate of 800kg / h~2680kg / h, an air flow rate of 400m / s~700m / s, a classifying wheel speed of 5000rpm~18000rpm, and a particle size D50 of the crushed ternary positive electrode material precursor is 50nm~500nm.

[0008] In some possible embodiments, after the step of mixing the ternary cathode material precursor with the lithium source to obtain a mixed material, the preparation method further comprises: The doping material is mixed with water and then sprayed on the surface of the mixed material for mixing. The doping material contains doping elements, and the doping elements include at least one of Na, K, F, Mg, Ca, Sr, Ba, Cu, Zn, Al, Ga, Ge, Se, Sn, Zr, Ti, Nb, V, P, Ta and Mo.

[0009] In some possible embodiments, the particle size D50 of the coating material satisfies: 1 nm <D50≤30nm。

[0010] In some possible embodiments, in the step of mixing the inner core with the coating material, the coating material is sprayed on the surface of the inner core in a spraying manner; and / or The temperature of the secondary sintering is 300° C. to 800° C., and the time of the secondary sintering is 10 h to 15 h.

[0011] In some possible embodiments, the mass ratio of the core to the solid electrolyte, the tin-containing oxide and the soluble cobalt salt is 1: (0.001-0.08): (0.001-0.08): (0.001-0.08).

[0012] In some possible embodiments, the solid electrolyte includes at least one of lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium niobium oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium aluminum titanium phosphate and lithium niobate; The tin-containing oxide includes at least one of tin dioxide, indium tin oxide and antimony tin oxide; The soluble cobalt salt includes at least one of cobalt acetate, cobalt nitrate, cobalt sulfate and cobalt chloride; The coating material also includes a dispersant, and the dispersant includes at least one of a polymer dispersant, an anionic wetting dispersant, a cationic wetting dispersant, an amphoteric wetting dispersant and a non-ionic wetting dispersant.

[0013] In some possible embodiments, the primary sintering includes pre-sintering and high-temperature sintering, the pre-sintering is sintering at a temperature of 400°C to 700°C for 10h to 15h, and the high-temperature sintering is sintering at a temperature of 600°C to 900°C for 15h to 20h.

[0014] An embodiment of the present application also provides a ternary positive electrode material, which is prepared by the aforementioned method for preparing the ternary positive electrode material. The ternary positive electrode material includes a core and a coating layer located on the surface of the core, wherein the core is a ternary positive electrode active substance, and the coating layer contains a solid electrolyte, tin and cobalt.

[0015] In addition, an embodiment of the present application further provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode active substance, and the positive electrode active substance is the aforementioned ternary positive electrode material.

[0016] Compared with the prior art, the preparation method of the ternary positive electrode material provided in the embodiment of the present application adopts a nano-scale high-nickel ternary positive electrode material precursor as a raw material, which can improve the specific capacity of the ternary positive electrode material. At the same time, the nano-scale particles are helpful for the transmission of lithium ions inside the ternary positive electrode material and reduce the internal resistance, thereby improving the rate performance of the ternary positive electrode material; moreover, the positive electrode material is surface coated with a mixed coating material of a solid electrolyte, a tin oxide and a soluble cobalt salt, and the coating layer is conducive to improving the structural stability, ion diffusion rate and electronic conductivity of the ternary positive electrode material. Therefore, the embodiment of the present application successfully achieves the compatibility of high specific capacity and high rate performance of the ternary positive electrode material by controlling the nickel content, optimizing the precursor particle size and the coating material composition. The electrochemical device using the ternary positive electrode material not only has a high energy density, but also has excellent power performance, which is suitable for high power and high energy density application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart of the method for preparing the ternary positive electrode material provided in an embodiment of the present application.

[0018] Figure 2 This is a schematic diagram of the structure of the electrochemical device provided in an embodiment of the present application.

[0019] Figure 3 This is a scanning electron microscope image of the ternary positive electrode material in Example 1 of the present application.

[0020] Figure 4 This is a scanning electron microscope image of the ternary positive electrode material in Example 2 of the present application.

[0021] Figure 5 This is a scanning electron microscope image of the ternary positive electrode material in Example 3 of the present application.

[0022] Figure 6 This is a scanning electron microscope image of the ternary positive electrode material in Comparative Example 1 of the present application.

[0023] Figure 7 This is a scanning electron microscope image of the ternary positive electrode material in Comparative Example 2 of the present application.

[0024] Figure 8 This is a comparison chart of the DC resistance test of button cells prepared with ternary positive electrode materials in Examples 1-3 of the present application and Comparative Examples 1-2. DETAILED DESCRIPTION

[0025] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0026] See also Figure 1 As shown, the present application embodiment provides a method for preparing a ternary positive electrode material, which specifically includes the following steps: Step S1, mixing a nanometer-scale ternary cathode material precursor with a lithium source to obtain a mixed material, and sintering the mixed material once to obtain a core, wherein the chemical formula of the ternary cathode material precursor is Ni α Co β Mnγ(OH) 2 , 0.8≤α<0.9, 0.1<β≤0.2, 0.01<γ≤0.1, and β+γ≤0.2.

[0027] Specifically, the nanometer-scale high-nickel ternary cathode material precursor is mixed evenly with the lithium source in a certain proportion, sintered once, and crushed after cooling to obtain the inner core. The molar amount of nickel element in the ternary cathode material precursor accounts for 80% or more of the total molar amount of transition metals, which is beneficial to improve the specific capacity of the ternary cathode material. The particles of the ternary cathode material precursor are controlled at the nanometer level, which reduces the particle size in the inner core, which is beneficial to shorten the transmission path of lithium ions, accelerate lithium ion transmission, and improve the rate performance of the ternary cathode material.

[0028] The preparation of nano-scale ternary positive electrode material precursor can be prepared by crushing the micron-scale ternary positive electrode material precursor. The crushing method can include using a high-speed air flow crusher, a sand mill or a ball mill, etc. It can be understood that the crushing method includes but is not limited to the above-mentioned method, and any crushing method that can reduce the particle size of the micron-scale ternary positive electrode material precursor to the nanometer level.

[0029] In this embodiment, the micron-sized ternary cathode material precursor is crushed into a nano-sized ternary cathode material precursor by air flow crushing, wherein the parameters of air flow crushing include: the feed rate can be 800kg / h~2680kg / h, the air flow rate can be 400m / s~700m / s, the classification wheel speed can be 5000rpm~18000rpm, and the particle size D50 of the ternary precursor after crushing can be 50nm~500nm. Air flow crushing uses high-speed airflow to accelerate the micron-sized ternary cathode material precursor material and make the materials collide, shear and rub against each other, so as to achieve the effect of controlling the particle size of the ternary cathode material precursor. The air flow crushing method has the advantages of precise particle size control, uniform particle size distribution and reduced particle agglomeration, which is conducive to the preparation of high-precision and well-dispersed nano-sized ternary cathode material precursors. The particle size D50 of the ternary precursor after crushing can further be 50nm~200nm, and can be illustratively 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or any value within the numerical range composed of any two of the above values.

[0030] The method of mixing the ternary cathode material precursor with the lithium source may include mixing, stirring or grinding with a high-speed mixer, etc., which can effectively mix the lithium source with the ternary cathode material precursor and promote the interaction between the two. It is understandable that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the lithium source and the ternary cathode material precursor is acceptable.

[0031] The ratio of the molar number of lithium in the lithium source to the total molar number of transition metals in the precursor of the ternary cathode material can be (1.04~1.06):1, which is conducive to the full incorporation of lithium ions during the formation of the inner core, promotes the uniform distribution of lithium ions in the inner core, and improves the electrochemical performance and structural stability of the ternary cathode material.

[0032] In some embodiments, the lithium source may include at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.

[0033] After the step of mixing the ternary positive electrode material precursor with the lithium source to obtain a mixed material, the preparation method may further include: spraying the mixed material with water on the surface of the mixed material and mixing, the mixed material contains a doping element, and the doping element may include at least one of Na, K, F, Mg, Ca, Sr, Ba, Cu, Zn, Al, Ga, Ge, Se, Sn, Zr, Ti, Nb, V, P, Ta and Mo. The above-mentioned doping material can reduce the agglomeration of the nano-scale particles of the ternary positive electrode material precursor during the sintering process, which is beneficial to maintaining the uniformity of the dispersion of the nano-scale particles of the ternary positive electrode material precursor. The doping element may further include at least one of Al, Ti, Mg and Mo. The method of spraying the mixed material with water and then mixing it on the surface of the mixed material is also beneficial to improve the uniformity of mixing the doping material and the mixed material.

[0034] The primary sintering may include pre-sintering and high-temperature sintering, the pre-sintering is sintering at a temperature of 400°C to 700°C for 10h to 15h, and the high-temperature sintering is sintering at a temperature of 600°C to 900°C for 15h to 20h. Specifically, the mixture of the ternary positive electrode material precursor and the lithium source may be pre-sintered first, and the pre-sintered product may be evenly dispersed before high-temperature sintering to obtain the inner core. Pre-sintering may melt the lithium source and fully infiltrate the inside of the ternary positive electrode material precursor, which is beneficial to improve the uniformity of the lithiation reaction; pre-sintering may also remove impurities such as water from the mixture, thereby increasing the production capacity of the high-temperature sintering section; high-temperature sintering may cause the mixture to form a complete layered crystal structure. The pre-sintering temperature may further be 450°C to 550°C, and may be exemplarily 400°C, 450°C, 470°C, 500°C, 530°C, 550°C, 600°C, 700°C, or any value within the numerical range composed of any two of the above values. The temperature of high temperature sintering can further be 750°C to 850°C, and can be illustratively 600°C, 700°C, 750°C, 770°C, 800°C, 820°C, 850°C, 900°C or any value within the numerical range formed by any two of the above values.

[0035] In some embodiments, the primary sintering atmosphere may be an oxygen-containing atmosphere, which is beneficial for the metal ions in the core to maintain an oxidized state. The primary sintering atmosphere may further be an oxygen-rich atmosphere or a pure oxygen atmosphere.

[0036] Step S2, mixing and grinding the solid electrolyte, the tin-containing oxide and the soluble cobalt salt to obtain a coated material.

[0037] Specifically, first, a solid electrolyte, a tin-containing oxide, and a soluble cobalt salt are added to an appropriate amount of water, mixed evenly, and then ground. Ultrasonic waves can also be used for further dispersion to obtain a coating material. The ground coating material can improve the dispersibility of the coating material and reduce the particle size of the coating material, which is beneficial to further reducing the particle size of the ternary cathode material and accelerating the insertion and extraction of lithium ions in the ternary cathode material.

[0038] In some embodiments, the solid electrolyte may include at least one of lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium niobium oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium titanium aluminum phosphate, and lithium niobate. The solid electrolyte can inhibit side reactions with the electrolyte, improve the interfacial stability and cycle life of the ternary cathode material; it can also enhance the ionic conductivity of the ternary cathode material, thereby improving the rate performance of the ternary cathode material.

[0039] In some embodiments, the tin-containing oxide may include at least one of tin dioxide, indium tin oxide, and tin antimony oxide. The tin-containing oxide can improve the structural stability and conductivity of the ternary cathode material, which is beneficial to improving the cycle life and rate performance of the ternary cathode material.

[0040] In some embodiments, the soluble cobalt salt may include at least one of cobalt acetate, cobalt nitrate, cobalt sulfate, and cobalt chloride. The soluble cobalt salt is beneficial to reducing the interfacial impedance of the ternary cathode material and improving the capacity and rate performance of the ternary cathode material.

[0041] In some embodiments, grinding may include sand grinding or ball grinding. It can be understood that the grinding method includes but is not limited to the above methods.

[0042] In some embodiments, the particle size D50 of the coating material may satisfy: 1 nm < D50 ≤ 30 nm. Utilizing the high surface energy and large specific surface area of the coating material nanoparticles is beneficial to improving the coating effect of the coating material on the ternary cathode material and further improving the rate performance of the ternary cathode material; moreover, the smaller particle size of the coating material can further control the particle size of the ternary cathode material and improve the specific capacity of the ternary cathode material. The particle size D50 of the coating material may further be 5 nm to 30 nm, and exemplarily, it may be any value within the numerical range composed of any two of the values 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm or above.

[0043] In some embodiments, the coating material may further include a dispersant, which may include at least one of a polymer dispersant, an anionic wetting dispersant, a cationic wetting dispersant, an amphoteric wetting dispersant, and a nonionic wetting dispersant. The above-mentioned dispersant can reduce the aggregation of nanoparticles in the coating material, which is beneficial to obtaining a thin and uniform coating layer. Exemplarily, the dispersant may include at least one of polyvinyl alcohol, sodium lauryl sulfate, cetyltrimethylammonium bromide (CTAB), oleamide propyl betaine, and dodecanol. It can be understood that the dispersant includes but is not limited to the above materials.

[0044] Step S3: Mix the core with the coating material and perform secondary sintering to form a coating layer on the surface of the core, thereby obtaining a ternary cathode material.

[0045] Specifically, mix the core prepared in step S1 with the coating material prepared in step S2 evenly and perform secondary sintering to form a coating layer on the surface of the core, thereby obtaining a ternary cathode material. Since the core is prepared from a nanoscale ternary cathode material precursor and combined with the ground coating material, a thin and uniform coating layer can be formed. Therefore, this ternary cathode material has a small particle size and a uniform and dense coating layer, and has the characteristics of both high specific capacity and high rate performance.

[0046] Among them, the solid electrolyte in the coating layer can provide good ionic conductivity and reduce the transport resistance of lithium ions at the electrolyte contact interface; the tin-containing oxide is conducive to forming a conductive network, promoting the transport of electrons, and improving the overall conductivity of the ternary cathode material; the soluble cobalt salt can form a cobalt oxide layer, improving the electronic conductivity and ionic conductivity of the ternary cathode material and reducing the interface impedance. The solid electrolyte, tin-containing oxide, and soluble cobalt salt in the coating material synergistically improve the ion diffusion rate and electronic conductivity in the ternary cathode material, thereby improving the rate performance of the high-nickel ternary cathode material.

[0047] In addition, by controlling the particle size D50 of the coating material to satisfy 1 nm < D50 ≤ 30 nm, the coating effect can be further improved, and the rate performance and structural stability of the ternary cathode material can be enhanced.

[0048] In some embodiments, the mass ratio of the core to the solid electrolyte, tin-containing oxide, and soluble cobalt salt in the coating material is 1:(0.001~0.08):(0.001~0.08):(0.001~0.08), which is beneficial to optimizing the coating layer thickness; at the same time, adjusting the proportion of each component in the coating material is beneficial to the solid electrolyte, tin-containing oxide, and soluble cobalt salt to fully play their synergistic effects, which is beneficial to improving the comprehensive performance of the ternary cathode material.

[0049] In some embodiments, the mixing method may include spray coating, high-speed mixer mixing, stirring or grinding, etc., which can effectively mix the kernel with the coating material to promote the interaction between the two. Specifically, the present embodiment can adopt the method of spray coating, and adopt the method of wet spray coating to evenly spray the coating material on the surface of the kernel for uniform mixing and coating. Compared with dry coating, the coating effect of wet spray is more uniform. The mixture of the kernel and the coating material after spray coating can also be dried to achieve a better coating effect.

[0050] In some embodiments, the temperature of the secondary sintering can be 300°C to 800°C, which is conducive to forming a dense coating layer and promoting a tighter combination between the coating layer and the core. The temperature of the secondary sintering can further be 650°C to 750°C, and can be illustratively 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 700°C, 800°C or any value within the numerical range composed of any two of the above values.

[0051] In some embodiments, the secondary sintering time may be 10 h to 15 h, which is conducive to the formation of the coating layer. The secondary sintering time may further be 10 h to 12 h, and may be 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or any value within the numerical range composed of any two of the above values.

[0052] Compared with the prior art, the preparation method of the ternary positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By crushing the micron-scale ternary positive electrode material precursor to obtain a nano-scale ternary positive electrode material precursor, the particle size of the ternary positive electrode material is effectively reduced, the specific capacity of the ternary positive electrode material is improved, and at the same time, it is helpful for lithium ions to be deintercalated in the ternary positive electrode material, reducing the internal resistance of the ternary positive electrode material, thereby improving the rate performance of the ternary positive electrode material.

[0053] 2. By further adding doping materials to the ternary cathode material precursor, the agglomeration of the ternary cathode material precursor particles during the sintering process is reduced, which is beneficial to maintaining good dispersion of the ternary cathode material.

[0054] 3. By coating solid electrolyte, tin oxide and soluble cobalt salt, the lithium ion transfer rate and electronic conductivity of the ternary positive electrode material are further improved, thereby improving the rate performance of the ternary positive electrode material.

[0055] 4. Through the spray coating process, the effect of uniform coating on the surface of the inner core can be achieved, which is beneficial to improve the uniformity and density of the coating layer.

[0056] 5. This preparation method is simple and efficient, which is conducive to the large-scale production of ternary positive electrode materials and has excellent commercial prospects.

[0057] An embodiment of the present application also provides a ternary positive electrode material, which is prepared by the above-mentioned method for preparing the ternary positive electrode material. The ternary positive electrode material includes a core and a coating layer located on the surface of the core, wherein the core is a ternary positive electrode active substance, and the coating layer contains a solid electrolyte, tin and cobalt.

[0058] Compared with the existing technology, the ternary positive electrode material has a higher nickel content and a smaller particle size, and is coated with a solid electrolyte, tin and cobalt elements. Therefore, the ternary positive electrode material has both higher specific capacity and rate performance.

[0059] See also Figure 2 As shown, an embodiment of the present application also provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode plate 10, a negative electrode plate 20, a separator 30 and an electrolyte 40, wherein the positive electrode plate 10 includes a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described above.

[0060] The electrochemical device 100 prepared using the aforementioned ternary positive electrode material has the advantages of high energy density, high power, etc., and can be applied to electric vertical take-off and landing vehicles (EVTOL), meeting the dual requirements of high specific capacity and high power of batteries in the application scenarios of long-range, emergency landing and frequent use of EVTOL.

[0061] The above-mentioned ternary positive electrode material and its preparation method and electrochemical device are further described below through specific examples.

[0062] Example 1 Step 1: 10 kg of the precursor with a particle size D50 of 10.0 μm was crushed in a high-speed airflow mill. The airflow crushing parameters were: feed rate 2000 kg / h, airflow velocity 600 m / s, and classifier wheel speed 10000 rpm. The ternary cathode material precursor Ni with a particle size D50 of 0.4 μm was obtained. 0.8 Co 0.15 Mn 0.05 (OH) 2 , put the ternary cathode material precursor and 4780g lithium hydroxide monohydrate into a high-speed mixer and mix them evenly, then add 30g NH 4 F, 40g MgO, 25g BaO, 100gMoO 31.6 kg of water is evenly mixed and sprayed on the surface of the mixture of the ternary positive electrode material precursor and lithium hydroxide monohydrate to mix. After mixing evenly, sintering is performed once in an oxygen atmosphere, including pre-sintering at 500° C. for 11 hours and then high-temperature sintering at 820° C. for 14 hours to obtain the inner core.

[0063] Step 2: Mix 100 g of lithium lanthanum zirconium tantalum oxide, 50 g of tin dioxide, 800 g of cobalt acetate, 8 g of dispersant and 1.5 kg of water, grind with a sand mill until D50 is less than 30 nm, and further disperse with ultrasound to obtain a coated material.

[0064] Step 3: Spray the above-mentioned coating material onto the surface of the 10kg inner core, mix evenly in a high-speed mixer, dry, and perform secondary sintering at 750°C for 12h to obtain a ternary positive electrode material.

[0065] Example 2 Step 1: 10 kg of the precursor with a particle size D50 of 10.0 μm was crushed in a high-speed airflow mill. The airflow crushing parameters were: feed rate 2000 kg / h, airflow velocity 600 m / s, and classifier wheel speed 10000 rpm. The ternary cathode material precursor Ni with a particle size D50 of 0.4 μm was obtained. 0.85 Co 0.12 Mn 0.03 (OH) 2 The ternary cathode material precursor and 4737g lithium hydroxide monohydrate were put into a high-speed mixer and mixed evenly. Then 30g N 2 O 5 40g Li 3 PO 4 , 25gAl 2 O 3 、100g MoO 3 1.8 kg of water is evenly mixed and sprayed on the surface of the mixture of the ternary positive electrode material precursor and lithium hydroxide monohydrate to mix. After mixing evenly, sintering is performed once in an oxygen atmosphere, including pre-sintering at 490° C. for 11 hours and then high-temperature sintering at 810° C. for 14 hours to obtain the inner core.

[0066] Step 2: Mix 100 g of lithium lanthanum zirconium niobium oxide, 50 g of indium tin oxide, 800 g of cobalt nitrate, 10 g of dispersant and 2 kg of water, grind with a sand mill until D50 is less than 30 nm, and further disperse with ultrasound to obtain a coated material.

[0067] Step 3: Spray the above-mentioned coating material onto the surface of the 10kg inner core, mix evenly in a high-speed mixer, dry, and perform secondary sintering at 720°C for 12h to obtain a ternary positive electrode material.

[0068] Example 3 Step 1: 10 kg of precursor with a particle size D50 of 10.0 μm was crushed in a high-speed airflow mill. The airflow crushing parameters were: feed rate 2000 kg / h, airflow velocity 600 m / s, and classifier wheel speed 10000 rpm. The ternary cathode material precursor Ni with a particle size D50 of 0.3 μm was obtained. 0.88 Co 0.1 Mn0.02(OH) 2 , put the ternary cathode material precursor and 4700g lithium hydroxide monohydrate into a high-speed mixer and mix them evenly, then add 30g V doping material 2 O 5 40g T 2 O 5 , 25gSnO 2 、100gMoO 3 1.5 kg of water is evenly mixed and sprayed on the surface of the mixture of the ternary positive electrode material precursor and lithium hydroxide monohydrate to mix. After mixing evenly, sintering is performed once in an oxygen atmosphere, including pre-sintering at 480° C. for 10 hours and then high-temperature sintering at 800° C. for 14 hours to obtain the inner core.

[0069] Step 2: Mix 100 g of lithium lanthanum zirconium oxide, 50 g of antimony tin oxide, 1000 g of cobalt citrate, 10 g of dispersant and 2 kg of water, grind with a sand mill until D50 is less than 30 nm, and further disperse with ultrasound to obtain a coated material.

[0070] Step 3: Spray the above-mentioned coating material onto the surface of 10 kg of the inner core, mix evenly in a high-speed mixer, dry, and perform secondary sintering at 690° C. for 12 h to obtain a ternary positive electrode material.

[0071] Comparative Example 1 Step 1: 10 kg of ternary cathode material precursor Ni with a particle size D50 of 3.0 μm 0.33 Co 0.33 Mn 0.33 (OH) 2 Without nano-crystallization, directly with 4600g lithium carbonate, 30g V 2 O 5 40g T 2 O 5 , 25gSnO 2 、100gMoO 3 The mixture is put into a high-speed mixer for uniform mixing, and sintered once in an oxygen atmosphere, including pre-sintering at 700°C for 10 hours and then high-temperature sintering at 900°C for 14 hours, to obtain a core.

[0072] Step 2: Mix 10 kg of the kernel with 100 g of magnesium oxide, 50 g of titanium oxide, and 100 g of aluminum oxide in a high-speed mixer, and perform secondary sintering at 690° C. for 12 h to obtain a ternary positive electrode material.

[0073] Comparative Example 2 Step 1: 10 kg of ternary cathode material precursor Ni with a particle size D50 of 10.0 μm 0.85 Co 0.12 Mn 0.03 (OH) 2 Without nano-crystallization, directly with 4600g lithium carbonate, 30g V 2 O 5 40g T 2 O 5 , 25gSnO 2 、100g MoO 3 The mixture is put into a high-speed mixer for uniform mixing, and sintered once in an oxygen atmosphere, including pre-sintering at 500° C. for 10 hours and then high-temperature sintering at 730° C. for 14 hours, to obtain a core.

[0074] Step 2: Mix 10 kg of the kernel with 100 g of magnesium oxide, 50 g of titanium oxide, and 100 g of aluminum oxide in a high-speed mixer, and perform secondary sintering at 690° C. for 12 h to obtain a ternary positive electrode material.

[0075] The following tests were performed on the ternary positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-2.

[0076] Test method: 1. Scanning electron microscope (SEM) test: The ternary positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were observed using a scanning electron microscope.

[0077] 2. Rate performance test: The prepared ternary positive electrode material, conductive agent SP and mixed liquid NMP were mixed evenly in a mass ratio of 90:5:5. The speed of slurry pulling was 2000rpm for 90min. After coating and cutting, the pieces were vacuum dried at 120℃ for 12h and transferred to the glove box. The metal lithium sheet was used as the negative electrode and the battery shell was CR2032 to make a button battery. The constant current charge and discharge test was carried out using the LAND battery test system. During the test, the working voltage range of the first discharge capacity test was 2.0V~4.25V, the temperature was 25℃, the charge and discharge rates were +0.1C / -0.1C, +1C / -1C, +1C / -2C, +1C / -5C and +1C / -8C, and the CV cut-off current was 0.01C. The first discharge capacity of the battery prepared by the ternary positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 was measured, and the results are shown in Table 1.

[0078] 3. DC internal resistance (DCR) test: Use the button cell assembled in the rate performance test, calibrate the capacity at 25°C, and then discharge the button cell intermittently at a constant current of 155mA for 20 minutes, then leave it for 5 minutes, record the voltage drop ΔU between the battery voltage before the discharge is terminated and the battery voltage after the battery voltage stabilizes, and the discharge current, and then use the formula R=ΔU / I to calculate the DC internal resistance (where: ΔU is the voltage difference, R is the DC resistance, and I is the discharge current) to obtain the DCR value. The results are as follows: Figure 8 shown.

[0079] The above results show: like Figures 3 to 7 As shown, the surface morphology of the ternary positive electrode materials of Examples 1-3 and Comparative Examples 1-2 is compared. Compared with the agglomeration of particles and the large primary particles in Comparative Examples 1-2, the particle size of the ternary positive electrode material in Examples 1-3 is smaller and the dispersibility is better. The ternary positive electrode material in Example 1 has regular spherical particles, the primary particle size is less than 1 μm, and the dispersibility is better. This is because the particle size of the ternary positive electrode material precursor is controlled at the nanometer level in the embodiment and the agglomeration phenomenon is effectively reduced by the addition of doping materials. In addition, after dry coating and sintering in Comparative Examples 1-2, a significantly rough morphology is present, while after wet spray coating and sintering in Examples 1-3, the solid electrolyte, tin oxide, and soluble cobalt salt are uniformly coated on the particle surface, and the particle surface is relatively smooth, which indicates that the wet spray coating effect is more uniform and grinding the coated material to reduce the particle size is also conducive to improving the coating effect.

[0080] It can be seen from Table 1 that the discharge capacity of the batteries prepared with the ternary positive electrode materials in Examples 1-3 at different rates is higher than that of Comparative Examples 1-2. Among them, Comparative Example 1 is an existing common 111 high-power ternary material with good rate performance. At a discharge rate of 8C current density, the capacity of the battery in Comparative Example 1 is 140.1mAh / g, but the 0.1C capacity is relatively low, only 157.7mAh / g, which is difficult to meet the high energy density requirements of EVTOL batteries; Comparative Example 2 is an existing 8-series high-nickel ternary material, which has a relatively high 0.1C capacity of 213.9mAh / g, but its rate performance is relatively poor. At a current density of 8C, it is only 115.2mAh / g, which cannot meet the high power requirements of EVTOL batteries. The results of Example 2 and Comparative Example 1 show that the Ni prepared in Example 2 0.85 Co 0.12 Mn 0.03 O 2The ternary positive electrode material has a higher 0.1C capacity of 220.5mAh / g, and a discharge capacity of 195.3mAh / g at 8C. The initial capacity and rate performance are better than the 111 high-power ternary material in Comparative Example 1. The raw materials of Example 2 and Comparative Example 2 are the same Ni 0.85 Co 0.12 Mn 0.03 (OH) 2 Precursor, the results show that the 0.1C capacity of Example 2 is 220.5 mAh / g, which is higher than that of Comparative Example 2 (Comparative Example 2 is only 213.9 mAh / g); at a current density of 8C, the discharge specific capacity of Example 2 is 195.3 mAh / g, which is also better than that of Comparative Example 2 (Comparative Example 2 is only 115.2 mAh / g). Examples 1-3 nano-crystallize the precursor, spray-coat the solid electrolyte, tin oxide, soluble cobalt salt, etc., and at the same time improve the discharge specific capacity and rate performance of the high-nickel ternary positive electrode material. Among them, Examples 2 and 3 increase the nickel content on the basis of Example 1, and the discharge specific capacity of the ternary positive electrode material in Examples 2 and 3 is further increased.

[0081] from Figure 8 It can be seen that in Comparative Example 1, due to the high cobalt content, the DCR of the button cell prepared is small, but still reaches 7.2mΩ. In Comparative Example 2, the cobalt content is small, the particle size is large, the lithium ion diffusion is slow, and the DCR of the button cell prepared is high. Compared with Comparative Examples 1-2, the ternary positive electrode materials in Examples 1-3 improve the lithium ion diffusion rate and electronic conductivity of the ternary positive electrode materials by means of precursor nano-sizing and coating, effectively reducing the DCR of the prepared battery, which is beneficial to improving the power performance of the battery.

[0082] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a ternary positive electrode material, characterized in that: include: A nanometer-scale ternary cathode material precursor is mixed with a lithium source to obtain a mixed material, and the mixed material is sintered once to obtain a core, wherein the chemical formula of the ternary cathode material precursor is Ni α Co β Mnγ(OH)2, 0.8≤α<0.9, 0.1<β≤0.2, 0.01<γ≤0.1, and β+γ≤0.2; The solid electrolyte, the tin oxide and the soluble cobalt salt are mixed and ground to obtain a coated material; as well as The inner core and the coating material are mixed and subjected to secondary sintering to form a coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material.

2. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: Before the step of mixing the nanoscale ternary cathode material precursor with the lithium source and performing a sintering step, the preparation method further comprises: The ternary positive electrode material precursor is crushed by ball milling, sand milling or air flow crushing to obtain a nano-scale ternary positive electrode material precursor. The parameters of the air flow crushing include: a feed rate of 800kg / h~2680kg / h, an air flow rate of 400m / s~700m / s, a classifying wheel speed of 5000rpm~18000rpm, and the particle size D50 of the crushed ternary positive electrode material precursor is 50nm~500nm.

3. The method for preparing the ternary cathode material according to claim 1, characterized in that: After the step of mixing the ternary cathode material precursor with the lithium source to obtain a mixed material, the preparation method further comprises: The doping material is mixed with water and then sprayed on the surface of the mixed material for mixing. The doping material contains doping elements, and the doping elements include at least one of Na, K, F, Mg, Ca, Sr, Ba, Cu, Zn, Al, Ga, Ge, Se, Sn, Zr, Ti, Nb, V, P, Ta and Mo.

4. The method for preparing a ternary positive electrode material according to claim 1, characterized in that: The particle size D50 of the coated material satisfies: 1 nm <D50≤30nm。 5. The method for preparing the ternary cathode material according to claim 1, characterized in that: In the step of mixing the inner core with the coating material, the coating material is sprayed on the surface of the inner core in a spraying manner; the temperature of the secondary sintering is 300° C. to 800° C., and the time of the secondary sintering is 10 h to 15 h.

6. The method for preparing a ternary cathode material according to claim 1, characterized in that: The mass ratio of the core to the solid electrolyte, the tin-containing oxide and the soluble cobalt salt is 1: (0.001-0.08): (0.001-0.08): (0.001-0.08).

7. The method for preparing a ternary cathode material according to claim 1, characterized in that: The solid electrolyte comprises at least one of lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium niobium oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium aluminum titanium phosphate and lithium niobate; The tin-containing oxide includes at least one of tin dioxide, indium tin oxide and antimony tin oxide; The soluble cobalt salt includes at least one of cobalt acetate, cobalt nitrate, cobalt sulfate and cobalt chloride; The coating material also includes a dispersant, and the dispersant includes at least one of a polymer dispersant, an anionic wetting dispersant, a cationic wetting dispersant, an amphoteric wetting dispersant and a non-ionic wetting dispersant.

8. The method for preparing a ternary cathode material according to claim 1, characterized in that: The primary sintering includes pre-sintering and high-temperature sintering. The pre-sintering is sintering at a temperature of 400° C. to 700° C. for 10 h to 15 h, and the high-temperature sintering is sintering at a temperature of 600° C. to 900° C. for 15 h to 20 h.

9. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by the preparation method of the ternary positive electrode material as described in any one of claims 1 to 8, wherein the ternary positive electrode material comprises a core and a coating layer located on the surface of the core, wherein the core is a ternary positive electrode active material, and the coating layer contains a solid electrolyte, tin and cobalt.

10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described in claim 9.